Designing Postal Network Units - Josip Gracin; Antun Stipetić (Promet - Traffic&Transportation, 2012)
The existing postal infrastructure cannot efficiently support the requirements of new technologies and the supply of services on the open market of postal services. Post offices do not meet the new needs, therefore requiring an adjustment to new traffic and service requirements. The functioning of the postal system in the Republic of Croatia was carried out in order to adjust the functional equipment of the system to the introduction of the new technologies and services. At the same time a requirement was set to the public postal operator for more efficient performing of the universal postal service. Based on the analyses of the postal system functioning, a modular procedure of designing the postal network units was proposed and it provides the possibility of adjustment to the new technological, organizational and safety requirements of the postal system.KEY WORDS: postal units, module designing, postal traffic efficiency